Association of Cigarette Smoking with Depression and Anxiety in Middle-Aged Adults: a Large Cross-Sectional Study among Iranian Industrial Manufacturing Employees. - Alizadeh, Zeinab; Roohafza, Hamidreza; Feizi, Awat; Sarrafzadegan, Nizal (International Journal of Mental Health & Addiction, 2023)
This study aimed to examine the association of cigarette smoking with depression and anxiety in a large sample of formal and contractual employees of a mill steel company, Isfahan, Iran. This cross-sectional study was performed in 2014 among 3063 formal and contractual employees. Multi-stage cluster sampling along with stratified sampling based on managerial sections were employed for participants' selection. Data gathering was done by some validated Iranian version of self-administered questionnaires including, International Physical Activity – Short Form, Effort–Reward Imbalance, Hospital Anxiety and Depression Scale. The results showed in crude and adjusted models, smokers compared with never smoked had a higher risk of depression (crude OR: 1.45; 95% CI: 1.01–2.07 and adjusted OR: 1.52; 95% CI: 1.04, 2.23). Smoking was significantly associated with anxiety both in crude and adjusted models (OR: 1.66; 95% CI: 1.24, 2.23) and (OR: 1.74; 95% CI: 1.27, 2.38), respectively. Our study showed that the depression and anxiety were more prevalent in smoker workforce population than non-smokers. In order to reduce the current and future psychological disorders' burden among workforce population, it is needed to conduct mental health promotion and interventions such as effective smoking cessation programs.